Synthesis and Characterization of Zirconium Phosphate as a Solid Catalyst for Esterification of Wastewater Containing Acrylic Acid - M. R., Kamaruzaman; Chin, S. Y. (Asian Network for Scientific Information, 2014)
Commercially available heterogeneous catalyst such as ion exchange resin has been used by the industry in the esterification reaction to overcome the problems caused by homogeneous catalyst. Heterogeneous catalyst with high tolerance to water is needed in the esterification of wastewater containing carboxylic acid. Zirconium Phosphate is one of the solid catalyst with the characteristics of high water tolerance and high thermal stability. In the present study, Zirconium Phosphate was used to catalysed the esterification of wastewater containing acrylic acid. The catalysed was synthesized using sol-gel method and characterized using X-Ray diffraction analysis (XRD), physisorption analyzer (BET surface area), thermal analysis (TGA) and Field Emission Scanning Electron Microscope (FESEM). This catalyst was proven to yield has high conversion and it can be reused without any treatment.